Design and Preclinical Evaluation of Nicotine-Stearic Acid Conjugate-Loaded Solid Lipid Nanoparticles for Transdermal Delivery: A Technical Note - Jwala Renukuntla; Samuel Peterson-Sockwell; Bradley A. Clark; Nipunika H. Godage; Emanuela Gionfriddo; Pradeep Kumar Bolla; Sai H. S. Boddu (MDPI AG, 2023)
This study aimed to develop and evaluate nicotine--stearic acid conjugate-loaded solid lipid nanoparticles (NSA-SLNs) for transdermal delivery in nicotine replacement therapy (NRT). Nicotine conjugation to stearic acid prior to SLN formulation greatly increased drug loading. SLNs loaded with a nicotine-stearic acid conjugate were characterized for size, polydispersity index (PDI), zeta potential (ZP), entrapment efficiency, and morphology. Pilot in vivo testing was carried out in New Zealand Albino rabbits. The size, PDI, and ZP of nicotine-stearic acid conjugate-loaded SLNs were 113.5 ± 0.91 nm, 0.211 ± 0.01, and −48.1 ± 5.75 mV, respectively. The entrapment efficiency of nicotine-stearic acid conjugate in SLNs was 46.45 ± 1.53%. TEM images revealed that optimized nicotine-stearic acid conjugate-loaded SLNs were uniform and roughly spherical in shape. Nicotine-stearic acid conjugate-loaded SLNs showed enhanced and sustained drug levels for up to 96 h in rabbits when compared with the control nicotine formulation in 2% HPMC gel. To conclude, the reported NSA-SLNs could be further explored as an alternative for treating smoking cessation.